IMPROVING THE PROFESSIONAL STYLE OF SPEECH OF STUDENTS OF HIGHER EDUCATIONAL INSTITUTIONS - Xalilova Ruxsora Raupovna (American Journals Publishing, 2023)
The article is devoted to the main problems of professional communication at the university nowadays. It is quite understandable that in modern society the process of information transmitting becomes one of the most valuable knowledge areas. According to that modern university teacher has a great possibility not only to form the students’ intellect, but also to influence the process of their thinking, the process of information obtaining. Consequently, the ability of proper verbal communication can determine the future career of an engineer, even his whole life. The article also shows the research results, achieved by the scientists and the opinion of famous people on the point. The authors also describe the demands to a modern university teacher’s speech, the ways of teachers’ training to achieve the high level of speaking culture and the possibilities of such skills application.
Keywords: Professional speech, professional communication, verbal activity, verbal culture.